2021
DOI: 10.1071/hc21026
|View full text |Cite
|
Sign up to set email alerts
|

Health practitioner experience of Health and Disability Commissioner investigations

Abstract: INTRODUCTIONThe New Zealand Health and Disability Commissioner (HDC) Act 1994 was designed to protect the rights of consumers and provide a fair, simple, speedy, and efficient resolution to complaints. No recent studies have been published about the health practitioner experience of HDC investigations following a patient complaint, and none that include nurses and midwives. AIMTo use a restorative inquiry framework to understand the impacts and needs of health practitioners arising from an event that led to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The punitive steps the HDC can take at the conclusion of an investigation are limited and occur in a minority of investigations completed. However, research in New Zealand has shown that the process of undergoing an HDC investigation, even if it does not lead to censure, can be extremely emotionally distressing for clinicians and severely impact their personal and professional lives 9 . The more complex investigations often take around 2 years 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The punitive steps the HDC can take at the conclusion of an investigation are limited and occur in a minority of investigations completed. However, research in New Zealand has shown that the process of undergoing an HDC investigation, even if it does not lead to censure, can be extremely emotionally distressing for clinicians and severely impact their personal and professional lives 9 . The more complex investigations often take around 2 years 10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, research in New Zealand has shown that the process of undergoing an HDC investigation, even if it does not lead to censure, can be extremely emotionally distressing for clinicians and severely impact their personal and professional lives. 9 The more complex investigations often take around 2 years. 10 In 78% of the cases, the HDC recommended that the radiologist apologizes to the patient/family.…”
Section: Hdc Recommendationsmentioning
confidence: 99%
“…Some have argued that restorative processes should replace investigative processes (Cunningham, 2004; Wilkinson & Marshall, 2021), arguing health practitioners are ‘second victims’ in many cases of medical error (Wu, 2000) and are further harmed by these processes. For example, Wilkinson and Marshall argue that such a shift would mean:
‘The focus would change from: Which right has been breached?, who is responsible for the breach?, and what sanction will be applied?
…”
Section: Restorative and Responsive Mental Health Regulation: A Victo...mentioning
confidence: 99%
“…For example, Wilkinson and Marshall argue that such a shift would mean:
‘The focus would change from: Which right has been breached?, who is responsible for the breach?, and what sanction will be applied? to: What happened?, what impacts have there been?, and what is now needed to repair the harms and prevent further harm?’ (Wilkinson & Marshall, 2021, p. 8).
…”
Section: Restorative and Responsive Mental Health Regulation: A Victo...mentioning
confidence: 99%
See 1 more Smart Citation